Poetic Justice: A Case of Resolved Intractable Hiccups Following POEM for Achalasia. Issue 4 (April 2019) - Christian, Kaci; Wellington, Jennifer; Kim, Raymond; Quezada, Sandra; Xie, Guofeng
Abstract : Abstract: Achalasia is an esophageal motility disorder of impaired lower esophageal sphincter relaxation and absent peristalsis. The presenting symptoms are commonly dysphagia, chest pain, regurgitation, and weight loss. Hiccups have been associated with gastrointestinal diseases but uncommonly associated with achalasia. We present a 62-year-old man with a history of dysphagia, weight loss, and intractable hiccups. High-resolution impedance manometry revealed Type I achalasia, which was treated with per oral endoscopic myotomy. Postoperatively, his dysphagia, weight loss, and intractable hiccups resolved.